Techno-Economic Aspect of the Man-in-the-Middle Attacks - Zoran Cekerevac; Zdenek Dvorak; Ludmila Prigoda; Petar Cekerevac (Communications - Scientific letters of the University of Zilina, 2017)
This paper analyzes some aspects of the man-in-the-middle (MITM) attacks. After a short introduction, which outlines the essence of this attack, there are presented used scientific methods and hypotheses. The next chapter presents technology of MITM attacks and benefits that a successful attack provides the attacker with. Some of the most significant examples of such attacks, which have a larger scale and significant impact on the broader Internet community, are presented. This part of the article ends with an analysis of possible protection against MITM attacks. Later, on the basis of available data, the analysis of MITM attack from an economic point of view is given. In Conclusion, the summary of the whole analysis is performed.